Role of Biodiversity in Maintaining Ecological Equilibrium of Jharkhand - Murmu, Sona (American Journal of Biodiversity, 2026)
Jharkhand, a state in eastern India, represents a critical biodiversity hotspot with significant ecological importance for regional and national environmental stability. This research investigates the multifaceted role of biodiversity in maintaining ecological equilibrium across Jharkhand’s diverse ecosystems, including tropical forests, grasslands, and aquatic systems. Through comprehensive analysis of species distribution patterns, ecosystem services, and conservation challenges, this study demonstrates that biodiversity acts as the fundamental pillar supporting ecosystem resilience, carbon sequestration, water regulation, and livelihood sustainability. The research employs quantitative assessments of forest cover dynamics (2000-2023), species richness indices across eight major protected areas, and severity analysis of conservation threats. Key findings reveal that Jharkhand harbors approximately 3,500 flora species and 850 fauna species, with 127 endemic species contributing to unique ecological functions. The study documents a modest increase in forest cover from 29.61% (2000) to 29.67% (2023), while simultaneously identifying escalating threats from habitat fragmentation, mining activities, and climate change. Protected areas, particularly Palamau Tiger Reserve and Betla National Park, serve as critical biodiversity refugia but face mounting anthropogenic pressures. The research concludes that biodiversity conservation in Jharkhand requires integrated landscape management, community participation, and science-based policy interventions to sustain ecological equilibrium and ensure long-term environmental security.